2018
DOI: 10.1111/evo.13434
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in life span: Females homozygous for the X chromosome do not suffer the shorter life span predicted by the unguarded X hypothesis

Abstract: Life span differs between the sexes in many species. Three hypotheses to explain this interesting pattern have been proposed, involving different drivers: sexual selection, asymmetrical inheritance of cytoplasmic genomes, and hemizygosity of the X(Z) chromosome (the unguarded X hypothesis). Of these, the unguarded X has received the least experimental attention. This hypothesis suggests that the heterogametic sex suffers a shortened life span because recessive deleterious alleles on its single X(Z) chromosome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 52 publications
(82 reference statements)
0
25
0
Order By: Relevance
“…A recent study further shows that the heterogametic sex tends to exhibit higher mean/maximum lifespan across a wide taxonomic range, but phylogenetic signal and sexual selection could contribute to explain this relationship [10]. In addition, recent experimental evidence shows that “unguarding” the X chromosome in females erases the sex gap in lifespan in Drosophila melanogaster [11, 12] but see [13]. A second hypothesis focuses on the role of the heteromorphic Y (or W) chromosome.…”
Section: Mainmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study further shows that the heterogametic sex tends to exhibit higher mean/maximum lifespan across a wide taxonomic range, but phylogenetic signal and sexual selection could contribute to explain this relationship [10]. In addition, recent experimental evidence shows that “unguarding” the X chromosome in females erases the sex gap in lifespan in Drosophila melanogaster [11, 12] but see [13]. A second hypothesis focuses on the role of the heteromorphic Y (or W) chromosome.…”
Section: Mainmentioning
confidence: 99%
“…Moreover, this phenomenon influences chromatin integrity and gene expression profiles genome-wide [16], and is more acute in old males than in old females [17, 18]. Therefore, in D. melanogaster there is solid evidence of substantial “toxic Y” effects, via both the accumulation of deleterious mutations and repetitive DNA elements, resulting in increased mortality of the heterogametic sex [13, 14]. However, the role of the “toxic Y” hypothesis in explaining broad patterns of sex differences in ageing has yet to be addressed.…”
Section: Mainmentioning
confidence: 99%
“…However, it is difficult to imagine how these effects could mediate female-specific responses in reproductive aging when condition is altered, especially here where we controlled for maternal effects. No support for the unguarded-X hypothesis was found in the most direct test of this hypothesis yet (Brengdahl et al 2018a), but more indirect tests have found patterns consistent with this possibility (Pipoly et al 2015;Carazo et al 2016;Sultanova et al 2018). In any case, it also seems difficult to construct a scenario where X-linked recessive mutations could cause a response in female but not male reproductive aging when condition is altered.…”
Section: Genetic Quality and Sex-specific Aging 767mentioning
confidence: 99%
“…Here we briefly describe the creation of our A2 inbred lines; see figure S1B in Brengdahl et al (2018a) for more detail. We began by randomly sampling 44 males from a recently made replica of the Dahomey population that had a marked A2 balancer (CyO, Duox Cy , cn 2 , dpy lvl , pr 1 ) backcrossed into it and maintained in a heterozygous state.…”
Section: Creation Of Chromosome Homozygote Linesmentioning
confidence: 99%
“…According to the refugium hypothesis proposed here, we predict that in species with a high toxicity index (i.e., excess of intact TEs on the SLCs and/or paucity thereof in the rest of the genome) this toxic effect to be more accentuated (Figure 2A and B). The toxic-Y hypothesis has been recently investigated from a theoretical point of view in vertebrates with both XY and ZW systems [47] and put in contrast to the classic "unguarded-X" hypothesis [48][49][50], which proposes that the expression of recessive mutations on X/Z chromosomes is the cause of the shorter lifespan in the heterogametic sex. Sultanova et al [47] used the sizes of Y and W relative to X and Z as a proxy for toxicity, i.e., assuming that smaller SLCs are more repetitive.…”
Section: Sex-biased Implications For Mutational Loadmentioning
confidence: 99%